A The Influence of Financial Literacy, Overconfidence, and Risk Tolerance on Student Investment Decisions in Palembang City - Putri Fadillah Amanda Pufaa; Endah Dewi Purnamasari; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of financial literacy, overconfidence, and risk tolerance on investment decisions of students in Palembang City. This study uses quantitative methods and analysis using multiple linear regression analysis. Testing this study using SPSS version 25. The results of the first regression analysis prove that financial literacy (X1) has a positive and significant effect on investment decisions, If financial literacy increases, investment decisions also increase. The results of the second regression analysis prove that overconfidence (X2) has a positive and significant effect on investment decisions. If an investor has high overconfidence, the investment decision will also be high. The results of the third linear regression analysis prove that risk tolerance (X3) has no positive and significant effect. If an investor has a high risk tolerance, the investor will be more courageous in making investment decisions, whereas if an investor has a low risk tolerance, the investor tends to avoid risk.